(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Eritrea has traditionally farmed and utilized pepper, but it is an important element of the Eritrean culinary culture. Eritrean pepper germplasm has been revealed to be quite varied, with the ability to serve a wide range of applications and purposes. Pepper is well-known over the globe for its great nutritional value, health advantages, and therapeutic characteristics. It contains a lot of vitamins and minerals, as well as antibacterial and cancer-fighting capabilities. Chili pepper offers anti-cancer, anti therapeutic, anti-inflammatory, including antiinflammatory qualities for rheumatism, bronchitis stiff joints, or chest infections with cough as well as headache, arthritis, cardiac arrhythmias, and a range of other diseases. Even though medicinal plants are employed in Eritrea’s conventional healers, there is no proof that pepper was ever utilized as a medicinal plant. The purpose of this review was to raise awareness about the medicinal uses but also therapeutic properties of this well-known but also widely consumed power station to encourage studies into issues including such quality, safety, efficacy, as well as growth, or to prevent possible risks, especially those relating to aflatoxin contamination.